Case Report: A novel mutation in TNFAIP3 in a patient with type 1 diabetes mellitus and haploinsufficiency of A20 - Cao, Conghui; Fu, Xue; Wang, Xiaoli (Frontiers in Endocrinology, 2023)
Background Haploinsufficiency of A20 (HA20) is a monogenic autosomal-dominant genetic autoinflammatory disease caused by loss of function mutations in the TNFAIP3 gene. The predominant autoimmune phenotype associated with HA20 varies significantly, presenting with fever, recurrent oral and genital ulcers, skin rash, gastrointestinal and musculoskeletal symptoms, and other clinical manifestations, all of which indicate an early-onset of autoinflammatory disorder. Genetic linkage between TNFAIP3 and T1DM was reported in GWAS studies. However, only a few cases of HA20 combined with T1DM have been reported. Case description A 39-year-old man with a history of type 1 diabetes mellitus since 19 years was admitted to the Department of Endocrinology and Metabolism, First Affiliated Hospital of China Medical University. He also suffered from recurring and minor mouth ulcers since early childhood. His laboratory evaluation results revealed reduced islet function, normal lipid profile, HbA1c of 7%, elevated glutamate decarboxylase antibodies, elevated hepatic transaminases, and elevated thyroid-related antibodies with normal thyroid function. Notably, the patient was diagnosed in adolescence and never had ketoacidosis, the islets were functioning despite the long disease duration, his abnormal liver function could not be reasonably explained, and he had early onset Behcet’s-like disease symptom. Hence, although he was on routine follow-up for diabetes, we communicated with him and obtained consent for genetic testing. Whole-exome sequencing revealed a novel c.1467_1468delinsAT heterozygous mutation in the gene TNFAIP3, which is located in exon 7, resulting in a stop-gained type mutation p.Q490*. With good but mild fluctuating glycemic control, the patient received intensive insulin therapy with long-acting and short-acting insulin. The liver function was improved by using ursodeoxycholic acid 0.75 mg/d during the follow-up. Conclusion We report a novel pathogenic mutation in TNFAIP3 that results in HA20 in a patient with T1DM. In addition, we analyzed the clinical feathers of such patients and summarized the cases of five patients with HA20 co-presented with T1DM. When T1DM co-occurs with autoimmune diseases or other clinical manifestations, such as oral and/or genital ulcers and chronic liver damage, the possibility of an HA20 must be considered. Early and definitive diagnosis of HA20 in such patients may inhibit the progression of late-onset autoimmune diseases, including T1DM.